Treatment methods for converter sludge

By drying, mixing, baking, drying and roasting reduction of converter sludge, combining with the ratio control of carbon-containing raw materials, the problems of difficult treatment and low recycling rate of converter sludge are solved, and high efficiency is achieved Converter sludge recycling and high-quality production of metallized pellets.

CN115572828BActive Publication Date: 2025-02-07INST OF RES OF IRON & STEEL JIANGSU PROVINCE +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211375098.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-04
Publication Date
2025-02-07
Estimated Expiration
2042-11-04

AI Technical Summary

Technical Problem

In the prior art, there are problems such as difficulty in handling converter sludge and low recycling rate.

Method used

Through drying, mixing, baking, making, drying and roasting reduction, etc., the converter sludge is uniformly mixed with the carbon-containing raw materials to form a mixture with a binary alkalinity >2.5, and CaO-FeO is formed during the roasting and reduction process. Low melting point slag system structure, metallized pellets are generated.

Benefits of technology

The treatment volume, utilization rate and recycling efficiency of the converter sludge are greatly improved, and metallized pellets with good clumping performance and high consolidation strength are formed, which improves product quality and improves zinc recycling rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003926276450000061
    Figure BDA0003926276450000061
  • Figure BDA0003926276450000081
    Figure BDA0003926276450000081
Patent Text Reader

Abstract

The invention discloses a method for treating converter sludge, including drying and breaking, mixing, pelletizing, drying, roasting and reducing; in the converter sludge, the mass percentage of CaO is greater than 7%, the mass percentage of SiO2 is less than 3%, the mass percentage of T.Fe is greater than 45%, and the binary basicity of the converter sludge is greater than 4; in the mixing step, the converter sludge and the carbon-containing raw material are uniformly mixed into a mixture with a binary basicity greater than 2.5, the ratio of the number of atoms of elemental carbon in the mixture to the number of atoms of oxygen contained in the iron-containing oxide is 0.6-0.9, and the mass percentage of CaO is greater than 8%; the drying temperature is less than 350°C; the dry balls are sent into a rotary hearth furnace for roasting and reducing to obtain metallized pellets, and the secondary zinc oxide powder is recovered from the flue gas system of the rotary hearth furnace, the roasting temperature is 1200-1350°C, and the roasting time is greater than 8min. The invention solves the technical problems of difficult treatment and low recycling rate of converter sludge in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of slag metallurgy, and in particular relates to a method for treating converter sludge. Background Art

[0002] Converter steelmaking is the mainstream steelmaking process at present. Converter sludge is a byproduct captured by the wet dust removal system during converter steelmaking. Its output accounts for about 1.5% of crude steel output. In addition, since zinc-containing scrap steel is used in the converter steelmaking process, the zinc content in converter sludge is relatively high. Therefore, how to maximize the recycling of converter sludge has always been a problem that the steel industry wants to solve.

[0003] There are currently two main ways for steel companies to utilize converter sludge. One is to return it to the raw material system for sintering or pelletizing processes to replace part of the iron ore powder. However, this method will cause the non-ferrous metal elements, especially zinc, enriched in the converter sludge to return to the raw material system, resulting in an increase in the non-ferrous metal load of the raw materials entering the blast furnace, which is not conducive to the smooth operation and longevity of the blast furnace, and it is also easy to cause the harmful elements in it to continue to circulate and enrich in the steel production process. The other is to mix the converter sludge with iron-containing waste materials such as oxidized iron scale to make cold-consolidated pellets for use as coolants or slag-making agents for converter steelmaking. This utilization method has a low processing capacity for converter sludge, and due to the low strength of the cold-consolidated pellets, it often causes the converter dust removal system to be blocked. Summary of the invention

[0004] The object of the present invention is to provide a method for treating converter sludge to solve the technical problems of difficult treatment and low recycling rate of converter sludge in the prior art.

[0005] To achieve one of the above purposes, an embodiment of the present invention provides a method for treating converter sludge, characterized in that it comprises the following steps:

[0006] Drying and breaking up: drying the converter sludge and breaking it up into sludge particles, wherein the mass percentage of CaO in the converter sludge is greater than 7%, the mass percentage of SiO2 is less than 3%, the mass percentage of T.Fe is greater than 45%, and the binary basicity of the converter sludge is greater than 4;

[0007] Mixing: Evenly mix the converter sludge and the carbonaceous raw material into a mixture with a binary basicity of >2.5, and in the obtained mixture, the ratio of the number of atoms of elemental carbon to the number of atoms of oxygen contained in the iron-containing oxide is 0.6-0.9, and the mass percentage of CaO is >8%;

[0008] Ball making: the obtained mixture is made into green balls with a particle size of 15 to 30 mm;

[0009] Drying: Dry the obtained green balls at a temperature of less than 350°C;

[0010] Calcination reduction: the obtained dry balls are sent to a rotary hearth furnace for calcination reduction to obtain metallized balls, and secondary zinc oxide powder is recovered from the flue gas system of the rotary hearth furnace, wherein the calcination temperature is 1200-1350°C and the calcination time is >8min;

[0011] Wherein, binary basicity R = {CaO} / {SiO2}, {CaO} represents the mass of CaO, and {SiO2} represents the mass of SiO2.

[0012] As a further improvement of one embodiment of the present invention, the metallization rate of the metallized pellets is ≥50%, the compressive strength is >500N, and the dezincification rate is ≥95%.

[0013] As a further improvement of an embodiment of the present invention, in the drying and breaking up step, among the sludge particles, sludge particles with a particle size less than 1 mm account for >80%.

[0014] As a further improvement of one embodiment of the present invention, the carbon-containing raw material is at least one of blast furnace gas ash from a steel plant, coking dust ash, coal powder, and coke powder.

[0015] As a further improvement of one embodiment of the present invention, the carbon-containing raw material is in a granular form, wherein particles with a particle size less than 0.5 mm account for >95%.

[0016] As a further improvement of an embodiment of the present invention, the fixed carbon content of the carbon-containing raw material is greater than 30%.

[0017] As a further improvement of one embodiment of the present invention, the mixture is formed by mixing converter sludge and carbon-containing raw materials in a ratio of 7:3 to 9:1 by mass percentage, without adding a binder.

[0018] As a further improvement of one embodiment of the present invention, in the ball making step, the water content of the raw balls is ≤14%.

[0019] As a further improvement of one embodiment of the present invention, in the ball making step, a disc ball making machine is used to make the obtained mixture into raw balls.

[0020] As a further improvement of an embodiment of the present invention, in the drying step, the moisture content of the dry bulb is ≤2%.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: the converter sludge treatment method of the present invention, by controlling various treatment processes in combination with the control of the ratio of converter sludge to carbon-containing raw materials, especially controlling the ratio of the number of elemental carbon atoms in the converter sludge-carbon-containing raw material mixture to the number of atoms of oxygen contained in the iron-containing oxide, can achieve the reduction and utilization of the converter sludge-carbon-containing raw material mixture with a binary basicity>2.5, greatly increase the proportion of converter sludge in the mixture, thereby improving the treatment capacity, utilization rate and recycling efficiency of the converter sludge; and by adding a large proportion of converter sludge, a CaO-FeO low-melting-point slag system structure is formed during roasting reduction, ensuring that sufficient bonding phase is generated during the roasting process, so that the metallized pellets obtained by roasting reduction have good agglomeration performance and high consolidation strength, thereby improving the product quality of the metallized pellets. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.

[0023] An embodiment of the present invention provides a method for treating converter sludge, comprising the following steps:

[0024] (1) Drying and breaking up

[0025] The converter sludge is dried and then broken into sludge particles, specifically, a drying and breaking machine is used for drying, breaking and breaking. In the converter sludge, the mass percentage of CaO is greater than 7%, the mass percentage of SiO2 is less than 3%, the mass percentage of T.Fe is greater than 45%, and the binary basicity of the converter sludge is greater than 4.

[0026] Preferably, among the sludge particles, the sludge particles with a particle size of less than 1 mm account for >80%, so as to improve the agglomeration performance of the metallized pellets and avoid the irregular shape of the finally prepared metallized pellets.

[0027] (2) Mixing

[0028] The converter sludge and the carbonaceous raw material are mixed with water to form a mixture with a binary basicity of >2.5. Specifically, a strong mixer can be used to fully mix the mixture. In the obtained mixture, the ratio of the number of atoms of elemental carbon to the number of atoms of oxygen contained in the iron-containing oxide is 0.6-0.9, and the mass percentage of CaO is >8%, so that a certain low-melting slag phase is formed in the subsequent roasting and reduction process, thereby generating sufficient bonding phase to ensure that the metallized pellets finally prepared have good consolidation effect and balling properties, and do not pulverize or break during cooling and transportation.

[0029] Specifically, the carbon-containing raw material is at least one of blast furnace gas ash, coking dust ash, coal powder, and coke powder in a steel plant, so as to ensure that it contains sufficient carbon content to achieve efficient recycling of converter sludge. In particular, the use of blast furnace gas ash and coking dust ash in a steel plant can also achieve the recycling of steel smelting by-products, reduce environmental pollution, and has important environmental protection significance.

[0030] Preferably, the carbon-containing raw material is in a granular form, wherein particles with a particle size of less than 0.5 mm account for >95%, which can further improve the agglomeration performance of the metallized pellets.

[0031] Preferably, the fixed carbon content of the carbon-containing raw material is >30%, which can reduce the proportion of carbon-containing raw materials used and improve the proportion of converter sludge used and the treatment efficiency while ensuring that the ratio of the number of elemental carbon atoms in the mixture to the number of oxygen atoms contained in the iron-containing oxide meets the requirement of 0.6 to 0.9.

[0032] Preferably, the mixture is formed by mixing converter sludge and carbonaceous raw materials in a ratio of 7:3 to 9:1 by mass percentage, and no binder is needed. By adding a large proportion of converter sludge to the mixture, not only can the recovery rate and treatment efficiency of converter sludge be improved, and a large amount of converter sludge accumulation can be avoided, but also the amount of metallurgical dust removal ash with poor formability added to the mixture can be reduced, and the high viscosity of converter sludge can be utilized, so that the mixture does not need to be additionally added with a binder during the pelletizing process, thereby reducing production costs.

[0033] (3) Ball making

[0034] The obtained mixture is made into green balls with a particle size of 12 to 16 mm. On the one hand, the heat transfer rate can be guaranteed and the reduction efficiency can be improved. On the other hand, it can avoid the green balls having too large a particle size, which leads to poor thermal conductivity and is not conducive to the reduction reaction.

[0035] Preferably, the moisture content of the green balls is ≤14%, so as to facilitate subsequent drying and save drying time.

[0036] Preferably, a disc pelletizing machine is used to make green pellets from the obtained mixture to reduce costs.

[0037] (4) Drying

[0038] The obtained green balls are dried using a chain grate, and the drying temperature is ≤350℃ to avoid the green balls bursting due to excessive drying temperature.

[0039] Preferably, the moisture content of the dry balls is ≤2% to reduce the explosion during the pellet roasting process.

[0040] (5) Calcination reduction

[0041] The obtained dry balls are sent to a rotary hearth furnace for roasting and reduction to obtain metallized pellets, and secondary zinc oxide powder is recovered from the flue gas system of the rotary hearth furnace. The roasting temperature is 1200-1350°C and the roasting time is >8min to avoid the pellets sticking due to too high temperature and the reduction efficiency being low due to too low temperature.

[0042] Wherein, binary basicity R = {CaO} / {SiO2}, {CaO} represents the mass of CaO, and {SiO2} represents the mass of SiO2.

[0043] The treatment method controls various treatment processes in combination with the ratio of converter sludge to carbon-containing raw materials, especially controls the ratio of the number of elemental carbon atoms in the converter sludge-carbon-containing raw material mixture to the number of atoms of oxygen contained in iron-containing oxides, so as to achieve reduction and utilization of the converter sludge-carbon-containing raw material mixture with a binary basicity of >2.5, greatly increase the proportion of converter sludge in the mixture, and thus improve the treatment capacity, utilization rate and recycling efficiency of the converter sludge; and by adding a large proportion of converter sludge, a CaO-FeO low-melting-point slag system structure is formed during roasting and reduction, ensuring that sufficient bonding phase is generated during the roasting process, so that the metallized pellets obtained by roasting and reduction have good agglomeration performance and high consolidation strength, thereby improving the product quality of the metallized pellets.

[0044] Specifically, the metallization rate of the metallized pellets obtained by the above treatment method is ≥50%, the compressive strength is >500N, and the dezincification rate is ≥95%. Not only can high-quality metallized pellets be prepared, but also the recovery rate of zinc is improved, and a large amount of zinc is avoided from remaining in the metallized pellets and then returning to the raw materials of the blast furnace, which leads to an increase in the non-ferrous metal load of the blast furnace, which is not conducive to the smooth operation and longevity of the blast furnace.

[0045] The technical solution of the present application is further described below in conjunction with some specific embodiments.

[0046] Example 1

[0047] (1) Drying and breaking up

[0048] The converter sludge was dried and crushed into sludge particles by a drying and breaking machine, wherein the sludge particles with a particle size of less than 1 mm accounted for more than 80%. The chemical composition of the converter sludge is shown in Table 1.

[0049] (2) Mixing

[0050] Blast furnace gas ash was selected as the carbon-containing raw material. The chemical composition of blast furnace gas ash is shown in Table 1 by mass percentage. The proportion of particles with a particle size of less than 0.5 mm in blast furnace gas ash is >95%. The converter sludge and blast furnace gas ash were mixed uniformly into a mixture by adding water in a mass percentage of 4:1 using a strong mixer, without adding a binder. The binary basicity of the obtained mixture was 4.48, and the mass percentage of T.Fe was 48.66%, the mass percentage of carbon was 9.77%, the mass percentage of CaO was 9.47%, and the ratio of the number of atoms of elemental carbon in the mixture to the number of atoms of oxygen contained in the iron oxide in the mixture was 0.6.

[0051] Table 1

[0052]

[0053] (3) Ball making

[0054] The obtained mixture is made into green balls with a particle size of 12 to 16 mm using a disc ball making machine, and the moisture content of the green balls is 13%.

[0055] (4) Drying

[0056] The obtained green balls are dried by a chain grate, the drying temperature is less than 350°C, and the moisture content of the dry balls is 2%.

[0057] (5) Calcination reduction

[0058] The obtained dry balls are sent to a rotary hearth furnace for roasting and reduction to obtain metallized balls, and secondary zinc oxide powder is recovered from the flue gas system of the rotary hearth furnace, wherein the roasting temperature is 1220-1310°C and the roasting time is >8min.

[0059] After testing, the metallization rate of the metallized pellets was 55%, the compressive strength was 1160N, and the dezincification rate was 95%.

[0060] Example 2

[0061] (1) Drying and breaking up

[0062] The converter sludge was dried and crushed into sludge particles by a drying and breaking machine, wherein the sludge particles with a particle size of less than 1 mm accounted for more than 80%. The chemical composition of the converter sludge is shown in Table 1.

[0063] (2) Mixing

[0064] Blast furnace gas ash was selected as the carbon-containing raw material. The chemical composition of blast furnace gas ash is shown in Table 1 by mass percentage. The proportion of particles with a particle size of less than 0.5 mm in blast furnace gas ash is >95%. The converter sludge and blast furnace gas ash were mixed uniformly into a mixture by adding water in a mass percentage of 18:7 using a strong mixer, without adding a binder. The binary basicity of the obtained mixture was 3.60, and the mass percentage of T.Fe was 46.65%, the mass percentage of carbon was 12.80%, the mass percentage of CaO was 9.07%, and the ratio of the number of atoms of elemental carbon in the mixture to the number of atoms of oxygen contained in the iron oxide in the mixture was 0.82.

[0065] (3) Ball making

[0066] The obtained mixture is made into green balls with a particle size of 12 to 16 mm using a disc ball making machine, and the moisture content of the green balls is 14%.

[0067] (4) Drying

[0068] The obtained green balls are dried by a chain grate, the drying temperature is less than 350°C, and the moisture content of the dry balls is 2%.

[0069] (5) Calcination reduction

[0070] The obtained dry balls are sent to a rotary hearth furnace for roasting and reduction to obtain metallized balls, and secondary zinc oxide powder is recovered from the flue gas system of the rotary hearth furnace, wherein the roasting temperature is 1220-1310°C and the roasting time is >8min.

[0071] After testing, the metallization rate of the metallized pellets was 63%, the compressive strength was 980N, and the dezincification rate was 99%.

[0072] Example 3

[0073] (1) Drying and breaking up

[0074] The converter sludge was dried and crushed into sludge particles by a drying and breaking machine, wherein the sludge particles with a particle size of less than 1 mm accounted for more than 80%. The chemical composition of the converter sludge is shown in Table 1.

[0075] (2) Mixing

[0076] Blast furnace gas ash and coking dust ash were selected as carbon-containing raw materials. The chemical compositions of blast furnace gas ash and coking dust ash are shown in Table 1, respectively, where the particle size of particles less than 0.5 mm accounts for >95%. A strong mixer was used to evenly mix converter sludge, blast furnace gas ash and coking dust ash into a mixture after adding water in a mass percentage of 15:4:1, without adding a binder. The binary basicity of the obtained mixture was 3.91, and the mass percentage of T.Fe was 46.03%, the mass percentage of carbon was 13.80%, the mass percentage of CaO was 9.04%, and the ratio of the number of atoms of elemental carbon in the mixture to the number of atoms of oxygen contained in the iron oxide in the mixture was 0.9.

[0077] (3) Ball making

[0078] The obtained mixture is made into green balls with a particle size of 12 to 16 mm using a disc ball making machine, and the moisture content of the green balls is 13%.

[0079] (4) Drying

[0080] The obtained green balls are dried by a chain grate, the drying temperature is less than 350°C, and the moisture content of the dry balls is 2%.

[0081] (5) Calcination reduction

[0082] The obtained dry balls are sent to a rotary hearth furnace for roasting and reduction to obtain metallized balls, and secondary zinc oxide powder is recovered from the flue gas system of the rotary hearth furnace, wherein the roasting temperature is 1220-1310°C and the roasting time is >8min.

[0083] The metallization rate of the metallized pellets was 75%, the compressive strength was 550N, and the dezincification rate was 99%.

[0084] Example 4

[0085] (1) Drying and breaking up

[0086] The converter sludge was dried and crushed into sludge particles by a drying and breaking machine, wherein the sludge particles with a particle size of less than 1 mm accounted for more than 80%. The chemical composition of the converter sludge is shown in Table 1.

[0087] (2) Mixing

[0088] Coal powder was selected as the carbon-containing raw material. The chemical composition of the coal powder is shown in Table 2 by mass percentage. The proportion of particles with a particle size of less than 0.5 mm in the coal powder is >95%. The converter sludge and coal powder were mixed uniformly into a mixture by adding water in a mass percentage of 5:1 using a strong mixer, without adding a binder. The binary basicity of the obtained mixture was 4.77, and the mass percentage of T.Fe was 44.74%, the mass percentage of carbon was 14.23%, the mass percentage of CaO was 8.82%, and the ratio of the number of atoms of elemental carbon in the mixture to the number of atoms of oxygen contained in the iron oxide in the mixture was 0.82.

[0089] Table 2

[0090]

[0091] (3) Ball making

[0092] The obtained mixture was made into green balls with a particle size of 12 to 16 mm using a disc ball making machine. The moisture content of the green balls was 12.5%.

[0093] (4) Drying

[0094] The obtained green balls are dried by a chain grate, the drying temperature is <350°C, and the moisture content of the dry balls is 1%.

[0095] (5) Calcination reduction

[0096] The obtained dry balls are sent to a rotary hearth furnace for roasting and reduction to obtain metallized balls, and secondary zinc oxide powder is recovered from the flue gas system of the rotary hearth furnace, wherein the roasting temperature is 1220-1310°C and the roasting time is >8min.

[0097] After testing, the metallization rate of the metallized pellets was 65%, the compressive strength was 986N, and the dezincification rate was 95%.

[0098] Example 5

[0099] (1) Drying and breaking up

[0100] The converter sludge was dried and crushed into sludge particles by a drying and breaking machine, wherein the sludge particles with a particle size of less than 1 mm accounted for more than 80%. The chemical composition of the converter sludge is shown in Table 1.

[0101] (2) Mixing

[0102] Coke powder was selected as the carbon-containing raw material. The chemical composition of coke powder is shown in Table 2 by mass percentage. The proportion of particles with a particle size of less than 0.5 mm in the coke powder is >95%. The converter sludge and coke powder were mixed uniformly into a mixture by adding water in a mass percentage of 20:3 using a strong mixer without adding a binder. The binary basicity of the obtained mixture was 4.61, and the mass percentage of T.Fe was 46.68%, the mass percentage of carbon was 13.02%, the mass percentage of CaO was 9.21%, and the ratio of the number of atoms of elemental carbon in the mixture to the number of atoms of oxygen contained in the iron oxide in the mixture was 0.75.

[0103] (3) Ball making

[0104] The obtained mixture is made into green balls with a particle size of 12 to 16 mm using a disc ball making machine, and the moisture content of the green balls is 13%.

[0105] (4) Drying

[0106] The obtained green balls are dried by a chain grate, the drying temperature is ≤350°C, and the moisture content of the dry balls is 2%.

[0107] (5) Calcination reduction

[0108] The obtained dry balls are sent to a rotary hearth furnace for roasting and reduction to obtain metallized balls, and secondary zinc oxide powder is recovered from the flue gas system of the rotary hearth furnace, wherein the roasting temperature is 1220-1310°C and the roasting time is >8min.

[0109] After testing, the metallization rate of the metallized pellets was 61%, the compressive strength was 1231N, and the dezincification rate was 95%.

[0110] Compared with the prior art, the beneficial effects of the present invention are as follows: the method for treating converter sludge of the present invention, by controlling various treatment processes in combination with the control of the ratio of converter sludge to carbon-containing raw materials, especially controlling the ratio of the number of elemental carbon atoms in the converter sludge-carbon-containing raw material mixture to the number of atoms of oxygen contained in iron-containing oxides, can achieve the reduction and utilization of the converter sludge-carbon-containing raw material mixture with a binary basicity>2.5, greatly increase the proportion of converter sludge in the mixture, thereby improving the treatment capacity, utilization rate and recycling efficiency of the converter sludge; and by adding a large proportion of converter sludge, a CaO-FeO low-melting-point slag system structure is formed during roasting reduction, ensuring that sufficient bonding phase is generated during the roasting process, so that the metallized pellets obtained by roasting reduction have good agglomeration performance and high consolidation strength, thereby improving the product quality of the metallized pellets.

[0111] The detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for treating converter sludge, characterized in that: The steps include: Drying and breaking up: drying the converter sludge and breaking it up into sludge particles, wherein the mass percentage of CaO in the converter sludge is greater than 7%, the mass percentage of SiO2 is less than 3%, the mass percentage of T.Fe is greater than 45%, and the binary basicity of the converter sludge is greater than 4; Mixing: The converter sludge and the carbon-containing raw material are uniformly mixed in a mass percentage of 7:3-9:1 to form a mixture with a binary basicity>2.5, without adding a binder. The carbon-containing raw material is at least one of blast furnace gas ash, coking dust ash, coal powder, and coke powder in a steel plant, and the ratio of the number of atoms of elemental carbon to the number of atoms of oxygen contained in the iron-containing oxide in the obtained mixture is 0.6-0.9, and the mass percentage of CaO is>8%; Ball making: the obtained mixture is made into green balls with a particle size of 12-16 mm; Drying: Dry the obtained green balls at a temperature of less than 350°C; Calcination reduction: The obtained dry balls are sent to a rotary hearth furnace for calcination reduction to obtain metallized balls, and secondary zinc oxide powder is recovered from the flue gas system of the rotary hearth furnace. The calcination temperature is 1200-1350°C and the calcination time is >8min. Among them, binary basicity R={CaO} / {SiO2}, {CaO} represents the mass of CaO, and {SiO2} represents the mass of SiO2.

2. The method for treating converter sludge according to claim 1, characterized in that: The metallization rate of the metallized pellets is ≥50%, the compressive strength is >500N, and the dezincification rate is ≥95%.

3. The method for treating converter sludge according to claim 1, characterized in that: In the drying and breaking up step, among the sludge particles, the sludge particles with a particle size less than 1 mm account for >80%.

4. The method for treating converter sludge according to claim 1, characterized in that: The carbon-containing raw material is in granular form, wherein particles with a particle size less than 0.5 mm account for >95%.

5. The method for treating converter sludge according to claim 1, characterized in that: The fixed carbon content of the carbon-containing raw material is >30%.

6. The method for treating converter sludge according to claim 1, characterized in that: In the ball making step, the moisture content of the raw balls is ≤14%.

7. The method for treating converter sludge according to claim 1, characterized in that: In the ball making step, a disc ball making machine is used to make raw balls from the obtained mixed material.

8. The method for treating converter sludge according to claim 1, characterized in that: In the drying step, the moisture content of the dry ball is ≤2%.

Citation Information

Patent Citations

  • Iron-smelting metallized pellets prepared by utilizing metallurgical dust and mud and production method thereof

    CN102337396A

  • Method for producing metallized pellets through iron mine tailings

    CN106755981A